Direct synthesis of 2-substituted benzimidazoles via dehydrogenative coupling of aromatic-diamine and primary alcohol catalyzed by a Co complex. (17th August 2020) - Zuo, Minghui; Guo, Weihao; Pang, Yucheng; Guo, Rui; Hou, Chuanfu; Sun, Shouneng; Wu, Hongfeng; Sun, Zhizhong; Chu, Wenyi
Abstract : A Co(ii ) complex was synthesized and used as catalyst to synthesize a series of 2-substituted benzimidazoles with o -phenylenediamines and primary alcohol as the substrates under mild reaction conditions. Abstract : A Co(ii ) complex with a stable structure was designed and synthesized with quinalic acid and Co (OAc)2 ·4H2 O. The single crystal structure of the complex was characterized by X-ray diffraction. A dehydrogenative coupling of aromatic diamines and primary alcohols was developed by using the Co(ii ) complex as the catalyst to synthesize 2-substituted benzimidazole. A series of 2-substituted benzimidazoles were obtained with good to excellent yields under mild reaction conditions. In addition, a compound with inhibitory Parkinson's activity was synthesized on a gram-scale by using this method. Finally, the reaction mechanism was proposed and the energy changes in the reaction process were simulated by density functional theory (DFT).